1994
DOI: 10.7326/0003-4819-121-12-199412150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Improves Endothelium-Dependent, Flow-Mediated Vasodilation in Postmenopausal Women

Abstract: Short-term estrogen replacement therapy improves flow-mediated endothelium-dependent vasodilation in postmenopausal women. This improvement may be mediated by a direct effect of estrogen on vascular function or may be induced through modification of lipoprotein metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
155
3
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 651 publications
(174 citation statements)
references
References 0 publications
13
155
3
2
Order By: Relevance
“…The current study used a double-blind, randomised, placebocontrolled design with adequate power to detect small changes in clinic and ambulatory blood pressure produced by different doses of a C21 progestogen administered in a cyclical regimen in doses spanning the usual clinical dose range combined with a fixed daily dose of oral oestrogen. The results of the current study are consistent with those of previous studies, including the PEPI study, which have found no change [2][3][4][5][6][7][8][9][10]12 or a reduction [24][25][26]29 in blood pressure associated with the addition of a progestogen to 'replacement' doses of oestrogen.…”
Section: Discussionsupporting
confidence: 91%
“…The current study used a double-blind, randomised, placebocontrolled design with adequate power to detect small changes in clinic and ambulatory blood pressure produced by different doses of a C21 progestogen administered in a cyclical regimen in doses spanning the usual clinical dose range combined with a fixed daily dose of oral oestrogen. The results of the current study are consistent with those of previous studies, including the PEPI study, which have found no change [2][3][4][5][6][7][8][9][10]12 or a reduction [24][25][26]29 in blood pressure associated with the addition of a progestogen to 'replacement' doses of oestrogen.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, only male medical personnel were included in this study because menstrual cycle in women might have influenced the results of FMD measurements. 26,27 Further investigation was necessary to clarify whether similar results were observed in women. In addition, this study was focused on the short-term effect of aromatherapy on endothelial dysfunction after night-shift work.…”
Section: Study Limitationsmentioning
confidence: 88%
“…Experiments in laboratory animals proved that oestrogens dilate the large arteries. 28,29 In peri-and postmenopausal women, [30][31][32] they widen the smaller resistance vessels 33 by mechanisms that include the protection of endothelial function, 31 the potentiation of nitric oxide release 30,32 and the modulation of sympathetic reactivity. 24,34 Oestrogens may also influence the viscoelastic properties of the arterial wall by changing the relative proportions of collagen and elastin, 35 by inhibition of smooth muscle cell proliferation, or by the prevention of atherosclerotic stiffening.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the sample had been stratified by sex and age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), 褍60 years), in an attempt to recruit the same number of subjects in each stratum. Households were identified from population registries as persons who shared the same address.…”
Section: Study Populationmentioning
confidence: 99%